Catholicity and education: notes for a Catholic reading of education as formation from the personal experience of love (2021)
It is common to listen to that a big part of the education crisis the world has been going through since some decades ago, is a product of the “architectural” system, inspired by the meta-recount which provided us the herramental rationality and the pedagogical ways instilled by the uniquetrue educational and religious tradition, a single pedagogy and a single manner to relate with knowledge, which turn out to be a damaging mixture triggering identity and pertinence unbalances on an educational basis, finally carrying out to a problematic issue that we as lecturers and students are having with the most terrible consequences. In this paper, we are aimed to argue that policies certainly can not be followed as those that formerly educated modernity youngsters, but also the problem is not finally a pedagogical method coming up from the philosophical, scientific and religious conception about education, but precisely on the signification in itself and how that education sense searching is taken; so from the experience revealing in every educational fact, it is understood not only as learning, but also as instructing or formation. Therefore, more than a “pedagogical procedure” problem, education is a today’s sense, personal experience and intersubjective problem about the teaching conception, this way, beyond defending a “catholic model” for education, this paper proposes to show “the experiencing and whole presence of love” –this is our expression- like eros, philia and agape, “contemporary” catholicity essential base, builds itself through a renewed, pertinent and appropriated way for backing education in the present.